Strategies for identifying familial hypercholesterolaemia in non-specialist clinical settings - Qureshi, Nadeem; Weng, Stephen F.; Tranter, Jennifer A.; Da Silva, Maria L.; Kai, Joe; Leonardi-Bee, Jo (Wiley, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: